Peningkatan Motivasi Dan Hasil Belajar Mata Pelajaran Penjasorkes Materi Permainan Bola Voli Melalui Model E’i Berbantuan Gadis Desa Pada Siswa Kelas VII G SMP Negeri 2 Balapulang Semester Ganjil Tahun Pelajaran 2016/2017 - Winarko (Cakrawala: Jurnal Pendidikan, 2017)
T he aims of the research were improving learning motivation and achievement trough E’I Gadis Desa learning model.The research was action research. The research was done trough two cycles. There were three meetings in every cycle. The research involved 36 students of SMP Negeri 2 Balapulang in the academic year 2016/2017. The results of research showed the improvement on motivation and achievement. The percentage of students’ motivation increased from 61.9 % to 76.72 %, and the students’ achievement also increased from 61.11 to 86,11 % during two cycles. The research gives suggestions for teachers to use E’I Gadis Desa learning model to improve students’ motivation and achievement in teaching volley ball materials. In addition the teacher should notice the students’ grouping system, students’ cooperation spirit and management activities in the field while implementing E’I Gadis Desa learning model